Easy and hard functions for the Boolean hidden shift problem - Childs, A. M.; Kothari, R.; Ozols, M.; Rötteler, M.; Roetteler, Martin (Proceedings of the 8th Conference on Theory of Quantum Computation, Communication, and Cryptography (TQC'13), Guelph, ON, Canada, 2013)
We study the quantum query complexity of the Boolean hidden shift problem. Given oracle access to f(x+s) for a known Boolean function f, the task is to determine the n-bit string s. The quantum query complexity of this problem depends strongly on f. We demonstrate that the easiest instances of this problem correspond to bent functions, in the sense that an exact one-query algorithm exists if and only if the function is bent. We partially characterize the hardest instances, which include delta functions. Moreover, we show that the problem is easy for random functions, since two queries suffice. Our algorithm for random functions is based on performing the pretty good measurement on several copies of a certain state; its analysis relies on the Fourier transform. We also use this approach to improve the quantum rejection sampling approach to the Boolean hidden shift problem.